Sectoral responses, macroeconomic impact and household welfare: GST policy for the Malaysia economy / Juliana Mohd Abdul Kadir, Mohamed Aslam and Zarinah Yusof - Mohd Abdul Kadir, Juliana; Aslam, Mohamed; Yusof, Zarinah (Faculty of Accountancy, 2019)
Goods and services tax (GST) has been a controversial topic in Malaysia when it was first implemented. This study examines the impact of the GST on the Malaysian economy from three major perspectives. First, it investigates the consequent changes in sectoral responses, including output and prices for 15 main sectors. Second, the study presents the results of GST impact on seven macroeconomic variables, namely, consumption, investment, government revenue, government expenditure, export, import, and gross domestic product. Third, the results of household welfare are discussed. A computable general equilibrium model is utilized to simulate GST impact on the Malaysian economy, and a simple comparative static model is performed. The results prove that the higher the GST rate, the higher is the impact on each sector. The sectors most affected by GST are communication and ICT, and the electricity and gas sectors. By contrast, agriculture, forestry and logging, and the petroleum and natural gas sectors are the least affected. Consumption and investment receive the largest negative effect, whereas government revenue and expenditure show the largest positive effect. The study likewise finds that by lowering GST rate, the welfare loss was minimized and the higher-income groups were affected more than the lower-income groups.